Ginnalin A and hamamelitannin: the unique gallotannins with promising anti-carcinogenic potential - Rippin; Vikas Beniwal; Ajay Sharma; Bikram Jit Singh; Seema Ramniwas; Katrin Sak; Satish Kumar; Anil K. Sharma (Open Exploration Publishing Inc., 2023)
Tannins are secondary metabolites that belong to the family of polyphenolic compounds and have gained a huge interest among researchers due to their versatile therapeutic potential. After lignin, these are the second most abundant polyphenols found in almost every plant part like stem, bark, fruit, seed, leaves, etc. Depending upon their structural composition, these polyphenols can be divided into two distinct groups, namely condensed tannins and hydrolysable tannins. Hydrolysable tannins can be further divided into two types: gallotannins and ellagitannins. Gallotannins are formed by the esterification of D-glucose hydroxyl groups with gallic acid. The gallolyl moieties are bound by a depside bond. The current review focuses mainly on the anti-carcinogenic potential of recently discovered gallotannins, ginnalin A, and hamamelitannin (HAM). Both of these gallotannins possess two galloyl moieties linked to a core monosaccharide having anti-oxidant, anti-inflammatory, and anti-carcinogenic abilities. Ginnalin A is found in plants of the genus Acer whereas HAM is present in witch hazel plants. The biosynthetic pathway of ginnalin A along with the mechanism of the anti-cancer therapeutic potential of ginnalin A and HAM has been discussed. This review will certainly help researchers to work further on the chemo-therapeutic abilities of these two unique gallotannins.